Characterization of OmcA Mutants from Shewanella oneidensis MR‐1 to Investigate the Molecular Mechanisms Underpinning Electron Transfer Across the Microbe‐Electrode Interface - Neto, Sónia de Fátima Estevão (2018)
Electricity production in microbial fuel cells (MFCs) is an emerging green alternative to the use of fossil fuels. Shewanella oneidensis MR‐1 (SOMR‐1) is a Gram‐negative bacterium, adapted to MFCs due to its ability to link its bioenergetic metabolism through the periplasm to reduce extracellular electron acceptors. OmcA is a highly abundant outer‐membrane cytochrome of SOMR‐1 cells and is involved in the extracellular electron transfer to solid acceptors and electron shuttles. To investigate electron transfer performed by OmcA towards final acceptors, site directed mutagenesis was used to disturb the axial coordination of hemes. Interactions between OmcA and redox partners such as iron and graphene oxides, and electron shuttles were characterized using nuclear magnetic resonance and stopped‐flow experiments. Results showed that solid electron acceptors do not come into close proximity to the hemes, in agreement with experimentally observed slow electron transfer. In contrast, mutation of the distal axial ligand of heme VII changes the driving force of OmcA towards electron shuttles and reduces the affinity of the FMN:OmcA complex. Overall, these results reveal a functional specificity of particular hemes of OmcA and provide guidance for the rational design of mutated SOMR‐1 strains optimized for operating in different microbial electrochemical devices.